Synthetic lethality of Mycobacterium tuberculosis NADH dehydrogenases is due to impaired NADH oxidation - Yuanyuan Xu; Sabine Ehrt; Dirk Schnappinger; Tiago Beites (mBio, 2023)
ABSTRACTType 2 NADH dehydrogenase (Ndh-2) is an oxidative phosphorylation enzyme discussed as a promising drug target in different pathogens, including Plasmodium falciparum and Mycobacterium tuberculosis (Mtb). To kill Mtb, Ndh-2 needs to be inactivated together with the alternative enzyme type 1 NADH dehydrogenase (Ndh-1), but the mechanism of this synthetic lethality remained unknown. Here, we provide insights into the biology of NADH dehydrogenases and a mechanistic explanation for Ndh-1 and Ndh-2 synthetic lethality in Mtb. NADH dehydrogenases have two main functions: maintaining an appropriate NADH/NAD+ ratio by converting NADH into NAD+ and providing electrons to the respiratory chain. Heterologous expression of a water-forming NADH oxidase (Nox), which catalyzes the oxidation of NADH, allows us to distinguish between these two functions and shows that Nox rescues Mtb from Ndh-1/Ndh-2 synthetic lethality, indicating that NADH oxidation is the essential function of NADH dehydrogenases for Mtb viability. Quantification of intracellular levels of NADH, NAD, ATP, and oxygen consumption revealed that preventing NADH oxidation by Ndh-1/Ndh-2 depletes NAD(H) and inhibits respiration. Finally, we show that Ndh-1/Ndh-2 synthetic lethality can be achieved through chemical inhibition.IMPORTANCEIn 2022, it was estimated that 10.6 million people fell ill, and 1.6 million people died from tuberculosis (TB). Available treatment is lengthy and requires a multi-drug regimen, which calls for new strategies to cure Mycobacterium tuberculosis (Mtb) infections more efficiently. We have previously shown that simultaneous inactivation of type 1 (Ndh-1) and type 2 (Ndh-2) NADH dehydrogenases kills Mtb. NADH dehydrogenases play two main physiological roles: NADH oxidation and electron entry into the respiratory chain. Here, we show that this bactericidal effect is a consequence of impaired NADH oxidation. Importantly, we demonstrate that Ndh-1/Ndh-2 synthetic lethality can be achieved through simultaneous chemical inhibition, which could be exploited by TB drug development programs.